2017
DOI: 10.12681/bgsg.11173
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Geological Behaviour of Heterogeneous and Chaotic Rock Masses

Abstract: The engineering characterization of heterogeneous and complex geological formations for estimating their rock mass strength and deformability characteristics constitutes a challenge to geo-scientists and engineers dealing with the design and construction of slopes and tunnels. Mélanges and similar heterogeneous mixtures of hard blocks in weaker matrix, known as "bimrocks", present an overall strength significantly greater than the matrix strength, because the presence of rock blocks, above a threshold volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…), it could be much lower than this value. Previous findings from the literature [25,30,41,45,48,58,59] have indeed shown that C varied from 5 up to 24 for chalks, from about 7 to 21 for sandstones and from 13 to 15 for argillaceous rocks. Hence, a conversion factor equal to 14 was considered reliable and used for the mélange under study.…”
Section: Point Load Testsmentioning
confidence: 82%
“…), it could be much lower than this value. Previous findings from the literature [25,30,41,45,48,58,59] have indeed shown that C varied from 5 up to 24 for chalks, from about 7 to 21 for sandstones and from 13 to 15 for argillaceous rocks. Hence, a conversion factor equal to 14 was considered reliable and used for the mélange under study.…”
Section: Point Load Testsmentioning
confidence: 82%
“…When the volcanic formations are highly to totally weathered, usually clay rich soil formations are evident and slope instabilities in the form of rotational failures exist. Since weathered volcanic rocks and tuffs can produce block-in-matrix formations the block proportion in the soil mass can influence the geometry of the failure surface as it may be impeded by blocks (Medley and Sanz Rehermann, 2004;Tsiambaos, 2010).…”
Section: Composite Failures When Mixed Rockmentioning
confidence: 99%
“…Araştırmacılar tünel güzergahı boyunca gözlenmiş olan konglomera birimlerini "zayıf dayanımlı kaya" olarak tanımlamışlar ve tünel çalışmasında stabilite problemleri meydana getirebileceğini bildirmişlerdir. Tsiambaos [10], düşük dayanımlı bir matriks içerisinde yer alan sert tanelerin oluşturduğu bimrock (hamurda kaya) adıyla tanımlanan konglomeratik çökellerin mühendislik jeolojisi özelliklerini ortaya koymuştur. Khanlari vd.…”
Section: Gi̇ri̇ş (Introduction)unclassified